1994
DOI: 10.2307/3350341
|View full text |Cite
|
Sign up to set email alerts
|

Client Outcomes II: Longitudinal Client Data from the Colorado Treatment Outcome Study

Abstract: The outcomes of a reform of the Denver mental health system, cosponsored by the state and the RWJF, are contrasted with changes in a comparison area of the state. The study examines the structural characteristics of the mental health system, staff attitudes and satisfaction, and client-reported services and outcome. Results indicate that, in Denver, structural changes, the introduction of new services, and an intervening financial crisis increased worker dissatisfaction. Client reports documented parallel chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(127 citation statements)
references
References 16 publications
(13 reference statements)
2
125
0
Order By: Relevance
“…Repeated measures analysis with generalized estimating equations (GEE) indicated that, over the 2-year follow-up period, ongoing DTR attendance was significantly associated with a greater likelihood of drug/alcohol abstinence after controlling for other pertinent variables such as sociodemographic characteristics, primary misused substance, severity of mental health symptoms, number of past hospitalizations for drug addiction or psychiatric problems, and traditional 12 step attendance. In addition to the main effect for DTR attendance, the analysis also found main effects on (higher) drug/alcohol abstinence for: pre-baseline abstinence; lower psychiatric symptom severity (as measured by the Colorado Symptoms Index, Shern et al, 1994); and not receiving inpatient treatment during the study period (Laudet et al, 2004a).…”
Section: Effect Of Dtr On Drug/alcohol Abstinencementioning
confidence: 87%
See 1 more Smart Citation
“…Repeated measures analysis with generalized estimating equations (GEE) indicated that, over the 2-year follow-up period, ongoing DTR attendance was significantly associated with a greater likelihood of drug/alcohol abstinence after controlling for other pertinent variables such as sociodemographic characteristics, primary misused substance, severity of mental health symptoms, number of past hospitalizations for drug addiction or psychiatric problems, and traditional 12 step attendance. In addition to the main effect for DTR attendance, the analysis also found main effects on (higher) drug/alcohol abstinence for: pre-baseline abstinence; lower psychiatric symptom severity (as measured by the Colorado Symptoms Index, Shern et al, 1994); and not receiving inpatient treatment during the study period (Laudet et al, 2004a).…”
Section: Effect Of Dtr On Drug/alcohol Abstinencementioning
confidence: 87%
“…Psychiatric symptom severity 13 Colorado Symptoms Index (Shern et al, 1994). E.g., "in the past month, how often have you: felt depressed?…”
Section: Installation Of Hope 12mentioning
confidence: 99%
“…These covariates are derived from either the baseline interview data or administrative data. The variables available for inclusion in Z were socio-demographics (e.g., age, gender, race/ethnicity, marital and parental status, education, employment, and income); social support ( Shern et al, 1994], range = 15-75, Cronbach alpha = 0.89); criminal and incarceration history (i.e., number of arrests and having a prison stay prior to baseline); whether the offender had a public attorney; and supervision type and intensity (e.g., number of completed and incomplete contacts with probation, and number of drug tests taken and number of positive tests). Some of these covariates, specifically measures of supervision and drug test results change over time; all other measures reflect an offender's situation at baseline and are therefore fixed in each time period.…”
Section: Discussionmentioning
confidence: 99%
“…The Colorado Symptom Index (CSI); 29 The GAIN Substance Problems Scale (GAIN SPS) 30 The Vocational Time-Line Follow-Back Questionnaire (VTLFB) 31 The Comorbid Conditions (CMC) list [32][33][34] The Community Integration Scale (CIS) [35][36][37] The Health, Social, Justice Service Use (HSJSU) inventory.…”
Section: Methodsmentioning
confidence: 99%